Mega-Trends Impacting Food Security and Nutrition: A Global Experience - Fan, Shenggen (2018)
Shenggen Fan Transforming Agriculture and Food systems for Higher Income and Better Nutrition: Global and Emerging Perspective, IFPRI-JICA Workshop June 28, 2018